Literasi Kebijakan Pemekaran Wilayah Di Kabupaten Bengkulu Tengah - Hamid, Anwar; Anggraini, Cici; Tomi, Belsa Eksan; Marsindo, Haji; Asisko, Vego (Jurnal Kewirausahaan dan Bisnis, 2023)
This activity aims to describe regional expansion policies, factors that support the implementation of regional expansion policies, analyze the form of policy implementation in the political, economic and socio-cultural fields, and analyze the implementation of regional expansion policies in supporting national integration in Bengkulu City. Factors that support the implementation of regional expansion policies are the existence of potential natural resources, investment, transportation and communication infrastructure, openness to outsiders and public support (community). The form of policy implementation in the political field includes the development of various political structures and infrastructure, transparency and accountability of government, increasing the role and active participation of the community in the decision-making process, freedom of politics and organization, upholding the rule of law and human rights, and realizing political stability. The economic sector includes accelerating the development of economic structures and infrastructure, managing the potential of natural resources and increasing employment, per capita income, Gross Regional Domestic Product and Regional Original Income. In the socio-cultural field, this includes fostering harmony among citizens, reducing socio-cultural gaps, improving the quality of education, regional structuring capabilities and empowering community groups, developing local cultural values and utilizing local wisdom in solving various problems. The implementation of regional expansion policies supports national integration in the city of Bengkulu, because; the realization of the stability of community life, the ease of obtaining public services, the increasing quality of public services, and the realization of integration in community life.